Ontological semantic agent in the context of big data: A tool applied to information retrieval in scientific research - Coneglian, Caio Saraiva [UNESP]; Fusco, Elvis; Segundo, José Eduardo Santarém; Junior, Valdir Amancio Pereira; de Castro Botega, Leonardo (Springer Nature, 2016)
The large increase in the creation and dissemination of data on the Internet can offer information of high value-added to organizations. This information can be provided by heterogeneous databases that may not be considered relevant by most systems, e.g., social media data, blogs and more. If organizations would use such sources, they could build a new management vision known as Competitive Intelligence. In the context of architectures of Information Retrieval, this research aims on implementing a semantic extraction agent for the Web environment, allowing information finding, storage, processing and retrieval, such as those from the Big Data context produced by several informational sources on the Internet, serving as a basis for the implementation of information environments for decision support. Using this method, it will be possible to verify that the agent and ontology proposal addresses this part and can play the role of a semantic level of the architecture.
Keywords: Big Data; Ontology; Semantic agent; Semantic web